2003
DOI: 10.1074/jbc.m211661200
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Zipper Domain Targets cAMP-dependent Protein Kinase to Mammalian BK Channels

Abstract: Large conductance, calcium-and voltage-activated potassium (BK) channels control excitability in many tissues and are regulated by several protein kinases and phosphatases that remain associated with the channels in cell-free patches of membrane. Here, we report the identification of a highly conserved, non-canonical, leucine zipper (LZ1) in the C terminus of mammalian BK channels that is required for cAMP-dependent protein kinase ( Reversible protein phosphorylation represents a fundamental cellular regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…More recent experiments have identified a multi-protein signalling complex that is formed from a direct association of the BK Ca a subunit, b 2 -adrenoceptor and AKAP79/150 (now classified as AKAP5) through a mechanism that may involve leucine-zipper protein-protein interactions [101,102]. This unique signalling complex may also include an L-type voltagegated Ca 2+ channel (Ca v 1.2), resulting in a highly localised signalosome that mediates Ca 2+ -and phosphorylation-dependent modulation of BK Ca currents [101].…”
Section: Novel B 2 -Adrenoceptor Signalling In the Airways Ma Giembmentioning
confidence: 99%
“…More recent experiments have identified a multi-protein signalling complex that is formed from a direct association of the BK Ca a subunit, b 2 -adrenoceptor and AKAP79/150 (now classified as AKAP5) through a mechanism that may involve leucine-zipper protein-protein interactions [101,102]. This unique signalling complex may also include an L-type voltagegated Ca 2+ channel (Ca v 1.2), resulting in a highly localised signalosome that mediates Ca 2+ -and phosphorylation-dependent modulation of BK Ca currents [101].…”
Section: Novel B 2 -Adrenoceptor Signalling In the Airways Ma Giembmentioning
confidence: 99%
“…Here we measured the combined effect of both STREX and the β4 subunit. The experimental approach was to measure responses to dephosphorylation by alkaline phosphatase followed by cAMP + ATP application to measure effects of pKAdependent phosphorylation (BK channels in HEK cells have pKA pre-tethered to the channel and therefore do not require application of the catalytic enzyme (Tian et al, 2001, Tian et al, 2003). Because all data was paired, we could measure both effects on steady-state values (Fig.…”
Section: The β4 Subunit Confers Sensitivity To Dephosphorylation Of Smentioning
confidence: 99%
“…Recently, it was reported that ␤2 adrenergic receptor could simultaneously interact with both BK Ca and L-type Ca 2ϩ channels in vivo (Liu et al, 2004). Among intracellular signaling molecules in vertebrate, protein kinases and phosphatases, including PKA, protein kinase G, Src tyrosine kinase, Syk tyrosine kinase, focal adhesion kinase, and protein phosphatase 2A are most intensively studied as modulators of BK Ca channels functions (Dworetzky et al, 1996;Sansom et al, 1997;Alioua et al, 1998;Ling et al, 2000;Alioua et al, 2002;Rezzonico et al, 2002Rezzonico et al, , 2003Tian et al, 2003). Recently, Syntaxin1A and ␤-catenine also have been reported as direct binding partners of BK Ca channels.…”
Section: Introductionmentioning
confidence: 99%